Cover Feature: Recent Advances of CeO2‐Based Electrocatalysts for Oxygen and Hydrogen Evolution as well as Nitrogen Reduction (ChemElectroChem 6/2021). Issue 6 (15th February 2021) - Song, Xue‐Zhi; Zhu, Wen‐Yu; Wang, Xiao‐Feng; Tan, Zhenquan
Abstract : The Cover Feature shows the state‐of‐the‐art achievements of CeO2 ‐based electrocatalysts towards the oxygen evolution, hydrogen evolution, nitrogen reduction reactions (OER, HER, and NRR, respectively), highlighting the strategies to improve their performance, such as ion doping, interface and defect engineering, electronic structure optimization, and morphology control. More information can be found in the Review by X.‐Z. Song et al .